Explicit Instruction Berbantuan Wordwall: Strategi Membangun Kompetensi Kewarganegaraan Siswa SD - Lindha Puspitaning Cahya; Fadhil Purnama Adi; Deni Zein Tarsidi (Universitas Sebelas Maret, 2026)
This study aims to describe and analyze the implementation process of the Explicit Instruction learning model assisted by Wordwall media in supporting the civic competence of fifth-grade students at SDIT Al Anis in Pancasila Education learning. The civic competence examined consists of three main components, namely Civic Knowledge, Civic Skills, and Civic Disposition. This study used a qualitative approach with a case study design. The research subjects were the fifth-grade teacher and fifth-grade students at SDIT Al Anis, selected through purposive sampling. Data were collected through participatory observation, in-depth interviews, and documentation. Data analysis used the interactive model of Miles and Huberman with source and technique triangulation to ensure the validity of the data. The results showed that the implementation of the Explicit Instruction model assisted by Wordwall was able to support all three dimensions of civic competence in an integrated manner. In the Civic Knowledge dimension, the I Do–We Do –You Do syntax helped students build an understanding of Pancasila values gradually and contextually. In the Civic Skills dimension, group discussion activities and interactive Wordwall quizzes genuinely developed students' intellectual and participatory skills. In the Civic Disposition dimension, structured, experience-based learning authentically encouraged the growth of students' personal and public character. This study concludes that the integration of the Explicit Instruction model with the interactive digital media Wordwall is an effective and contextual approach for comprehensively developing the civic competence of elementary school students